“Estrategias lúdicas en la asignatura de ciencias naturales” - Azas Azogue, Elba Lourdes (2023)
Playfulness is an important element, since this characteristic is innate in children and development allows learning to be fun, this in turn provides a series of pleasant activities that relax and motivate. In the same way, at present the edition has been overshadowed because several teachers are not aware of the various playful strategies that can be implemented in the classroom. For this reason, playful strategies were applied to improve learning in the area of Natural Sciences in the students of the sixth grade of Basic Education of the Belisario Quevedo Educational Unit. located in the province of Cotopaxi. For this, the qualitative research methodology is used, with its four stages, as well as a case study that contributes to the collection of information, as well as an interpretive approach, an inductive and empirical method that helps to understand the educational reality through the descriptive and bibliographical research to analyze in depth through the technique and observation guide that allowed the information to be collected. In this way, the results achieved in the natural sciences class allowed us to identify gaps in the teaching-learning process due to the fact that decent students lack playful strategies in the PEA, which shows the difficulty in understanding content. therefore, making use of fun playful strategies allows improving learning in that area and thus achieving the desired learning objectives. This project will contribute to improving the teaching-learning process within the classroom as well. increase the teacher's didactic competence.